Security in cognitive radio networks - Qing-qi PEI; Hong-ning LI; Hong-yang ZHAO; Nan LI; Ying MIN (Tongxin xuebao)
Cognitive radio can obtain and access spectrum white holes without interfering primary users by sensing wireless environment to meet with the more spectrum requirement of users and improve spectrum utilization.However,it also brings new secure challenges that different from traditional wireless networks.Relying cognition cycle,the security issues in cognitive radio networks are presented from data channel,control channel and terminal equipment,then the existing defensive measures and propose the secure recommendations of cognitive radio networks are introduced.